Colonized masculinities and femicide in Latin America - Aguirre, Kathleen Kate Dominguez (Revista Crítica Histórica, 2022)
This article addresses studies on masculinities, gender violence and femicide in Latin America, based on theories from the Global South, with the aim of understanding how the modern-colonial gender system produces agents of death among colonized men. Through an intersectional and multicentered approach and based on the categories gender, masculinities, race, neoliberalism and necropolitics, the continuum of modern-colonial patriarchal violence is proposed to conceptualize a logical scheme of connection between the cycle of violence against the female gender to interpersonal level and the historical/global reproduction of a cycle of patriarchal violence of colonial origin that engenders an increase in the neoliberal stage, collecting systematic deaths of cis women, trans women and transvestites in Latin America.